2013
DOI: 10.1590/s0365-05962013000200029
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on melanonychia nail plate dermoscopy

Abstract: This statement, focused on melanonychia and nail plate dermoscopy, is intended to guide medical professionals working with melanonychia and to assist choosing appropriate management for melanonychia patients. The International Study Group on Melanonychia was founded in 2007 and currently has 30 members, including nail experts and dermatopathologists with special expertise in nails. The need for common definitions of nail plate dermoscopy was addressed during the Second Meeting of this Group held in February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 9 publications
1
57
0
2
Order By: Relevance
“…To overcome these limitations and increase the accuracy of diagnosis, the International Study Group on Melanonychia published official consensus statements with over a dozen diagnostic pearls based on dermoscopic images of the nail plate and hyponychium . In 2016, the International Dermoscopy Society reported clinical and dermoscopic clues to differentiate pigmented nail bands .…”
Section: Dermoscopic Features Of Adult Melanonychiamentioning
confidence: 98%
See 1 more Smart Citation
“…To overcome these limitations and increase the accuracy of diagnosis, the International Study Group on Melanonychia published official consensus statements with over a dozen diagnostic pearls based on dermoscopic images of the nail plate and hyponychium . In 2016, the International Dermoscopy Society reported clinical and dermoscopic clues to differentiate pigmented nail bands .…”
Section: Dermoscopic Features Of Adult Melanonychiamentioning
confidence: 98%
“…16,17 To overcome these limitations and increase the accuracy of diagnosis, the International Study Group on Melanonychia published official consensus statements with over a dozen diagnostic pearls based on dermoscopic images of the nail plate and hyponychium. 18 In 2016, the International Dermoscopy Society reported clinical and dermoscopic clues to differentiate pigmented nail bands. 19 Based on their original study, melanoma cases were significantly associated with six features: (i) width of the pigmented band of more than two-thirds of the nail plate; (ii) gray and black coloration; (iii) irregularly pigmented lines; (iv) Hutchinson's and micro-Hutchinson's signs;…”
Section: Dermoscopic Features Of Adult Melanonychiamentioning
confidence: 99%
“…In adulthood, the use of dermoscopy in the evaluation of nail pigmentation began in 2007, when dermoscopic criteria suggestive of benign and malignant nail melanocyte lesions were proposed [31], but it was later shown that the technique is not always reliable in the management of pigmented nail lesions [32]. The clinical ABCDEF rule for nail pigmentation [33] should always be applied with dermoscopy [22] for diagnostic accuracy.…”
Section: Alterations Of the Nail Platementioning
confidence: 99%
“…Except for melanonychia, [6][7][8][9][10][11][12][13][14] dermoscopy use in nail disorders is poorly established. However, application of this simple non-invasive tool to improve the diagnostic accuracy of OM should be explored.…”
Section: Introductionmentioning
confidence: 99%